Monocyte Chemoattractant Protein 1 is a Prognostic Marker in ANCA-Associated Small Vessel Vasculitis. (5th July 2009) - Ohlsson, Sophie; Bakoush, Omran; Tencer, Jan; Torffvit, Ole; Segelmark, Mårten
Abstract : Background . The (anti neutrophil cytoplasmatic autoantibody ANCA), associated small vessel vasculitides (ASVV) are relapsing-remitting inflammatory disorders, involving various organs, such as the kidneys. (Monocyte chemoattractant protein 1 MCP-1) has been shown to be locally up regulated in glomerulonephritis and recent studies have pointed out MCP-1 as a promising marker of renal inflammation. Here we measure urinary cytokine levels in different phases of disease, exploring the possible prognostic value of MCP-1, together with (interleukin 6 IL-6), (interleukin 8 IL-8) and (immunoglobulin M IgM). Methods . MCP-1, IL-6 and IL-8 were measured using commercially available ELISA kits, whereas IgM in the urine was measured by an in-house ELISA. Results . The MCP-1 levels in urine were significantly higher in patients in stable phase of the disease, compared with healthy controls. Patients in stable phase, with subsequent adverse events; had significantly higher MCP-1 values than patients who did not. MCP-1 and IgM both tended to be higher in patients relapsing within three months, an observation, however, not reaching statistical significance. Urinary levels of IL-6 correlated with relapse tendency, and IL-8 was associated with disease outcome. Conclusions . Patients with ASVV have raised cytokine levels in the urine compared to healthy controls, even during remission. Raised MCP-1 levels are associated with poor prognosis and possibly also with relapse tendency. The association with poor prognosis was stronger for U-MCP-1 than for conventional markers of disease like CRP, BVAS, and ANCA, as well as compared to candidate markers like U-IgM and U-IL-8. We thus consider U-MCP-1 to have promising potential as a prognostic marker in ASVV.